Characters in Film and Other Media - Eder, Jens (Open Book Publishers, 2025)
Characters are central to the creation and experience of films and other media. Their cultural significance is profound, but they also raise a wide range of questions. This book provides a comprehensive theory that guides the analysis and interpretation of characters across four dimensions: as represented beings with physical, psychological, and social characteristics; as artefacts with aesthetic structures; as meaningful symbols; and as symptoms of socio-cultural origins and effects. Integrating insights from film, media, and literary studies as well as philosophy, psychology and sociology, the book offers a broad range of approaches for understanding characters and the emotional responses they evoke. Richly illustrated and offering practical tools, along with case studies of numerous characters from different genres of films, this book will be invaluable to scholars and students of film and media studies and related disciplines, as well as artistic practitioners.